Human Resources Management Strategy in the Military Justice Environment: Study of State Civil Apparatus Management at the High Court of the Supreme Court of the Republic of Indonesia - Zidny Taqiyya; Asropi; Ratri Istania (International Journal of Science and Society, 2023)
The Supreme Court is a judicial institution vested with authority to exercise judicial power in four separate branches of the judiciary, namely the General Courts, Religious Courts, Administrative Courts, and Military Courts. The Military Court, in particular, serves as the judicial body responsible for upholding the law and justice for members of the Indonesian National Armed Forces (TNI). Unlike the other three branches of the judiciary, the Military Court system consists of three appellate courts and one main court. The existence of these four courts is governed by Law Number 31 of 1997 on Military Judiciary and the Chief Justice of the Supreme Court Regulation Number 125 of 2009 on the Delegation of Authority to High-Ranking Officials and Chief Justices of Appellate Courts within the Supreme Court for Signing in the Field of Personnel. However, the implementation of these regulations has still resulted in varying interpretations and paradigm differences, especially in understanding the phrase "appellate court," which has been perceived as somewhat biased and not fully implemented. This is particularly evident in the coordination and management of Civil Servants (ASN), as the Supreme Court places the Main Military Court on par with the appellate courts, although in practice, the Main Military Court resembles a "court above the appellate courts." This research employs a qualitative approach with a specific Case Study research method, focusing on the differential treatment of ASN members who represent a minority within the Military Judiciary. Ultimately, the study recognizes the need to bring together perspectives and unify understandings regarding the implementation of the Chief Justice of the Supreme Court Regulation Number 125 of 2009, analyzed through the Equal Employment Opportunity (EEO) theory, in order to harmonize the management and governance of appellate courts. This would help eliminate disparities between the High Military Court and the Main Military Court, serving as a bridge of understanding within the Military Judiciary in Indonesia.